Who's who: How "women of color" are (or are not) represented in STEM education research. Issue 2 (23rd December 2021) - Miles, Monica L.; Agger, Charlotte A.; Roby, ReAnna S.; Morton, Terrell R.
Abstract: Despite national calls for increasing diversity and inclusion within science, technology, engineering, and mathematics (STEM), inequitable recruitment and retention strategies remain commonplace. Inherent to many strategies is a lack of specificity in attending to the needs, desires, and cultures of individuals who are minoritized at the intersections of race, gender, and class through the use of broad, sweeping classifications such as "Women of Color." Using critical race feminism, we engaged in a meta‐synthesis of recent peer‐reviewed, empirical STEM education articles that used the term "Women of Color" to identify (a) how the term "Women of Color" was defined, (b) who was and was not represented by this term and (c) and how research findings accounted for the presence of WOC. We provide a critical discussion of how terminology is used and a call for specificity in equitable and justice‐oriented STEM programming.